The main prerequisites for the formation of the agricultural land market in Ukraine - Nadykto, Volodymyr; Надикто, Володимир Трохимович; Надыкто, Владимир Трофимович; Popova, Tetiana; Попова, Тетяна Вікторівна; Попова, Татьяна Викторовна (ФОП Однорог Т. В., 2019)
The prerequisites for the land market formation are identified. They include the provision of opportunities to buy lands only for physical persons; establishment of the maximum size and reasonable price of a land plot for the buyers; consideration of professionals in agriculture as potential buyers of lands; maintenance of a high level of soil fertility.
Keywords: agricultural land market; landowner; humus level in the soil; owner of land shares; soil fertility